THE EFFECT OF WORK SATISFACTORY ON TURN OVER INTENTION AND ORGANIZATIONAL COMMITMENT AS WELL AS ITS IMPACT TOWARD EMPLOYEE PERFORMANCE AT PT. BANK SULTENG - Prilly Rumbajan, Mouren Happy; Hasanuddin, Bakrie; Asngadi, Asngadi (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research intends to determine and to analyze the direct effect of work satisfaction on turn over intention and organizational commitment and its impact on the performance of employees at PT. Central Sulawesi Bank. The population consists of 87 people who are employees at Head Office PT. Bank Sulteng taken from all levels of employees. Data analysis in this research used Structural Equation Model (SEM). The results of the analysis using the SmartPLS ver 3.0 statistical tool reveals that work satisfaction has a positive and significant effect on tur nover intention. Work satisfaction has a positive and significant effect on organizational commitment. Work satisfaction has a positive and significant effect on employee performance. Turn over intention has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Work satisfaction has a positive and significant effect on performance through turn over intention as an intervening variable. Work satisfaction has a positive and significant effect on employee performance through organizational commitment as an intervening variable. Keywords: Work satisfaction, Turn over Intention, Organizational Commitment, Performance